A light, high-strength, heat-resistant high-entropy alloy and a preparation method thereof
By allocating CR, Al, V, NB, Ti, ZR, SI, SI elements in high-entropy alloys, the BCC single-phase organization is formed and the ZR-SI enhancement phase is used to solve the difficulty of achieving low density in the existing technology at the same time. High -strength and high -temperature problems have achieved efficient material performance improvement.
Patent Information
- Application Number
- CN202411590679.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The prior art is difficult to simultaneously realize low-density, high-strength and high-temperature resistant metal structural materials, which limits its further development and application in the actual engineering field.
By deploying the appropriate ratio of the seven elements of CR, AL, V, NB, Ti, ZR, and SI, a stable BCC single-phase tissue structure is formed, and ZR-SI reinforcement phase is used during the high temperature melting process to obtain light quality high-strength and strong resistance High entropy alloys.
The low density (density of less than 5.5 G/CM3), high -strength (room temperature resistance ≥ 1 GPA) and high temperature resistance (600 ° C high -temperature tensile strength ≥ 800 MPa, 800 ° C high -temperature resistance strength ≥ high temperature resistance (room temperature resistance strength ≥ 1 GPA) 500 MPa), suitable for heavy -duty applications.
Smart Images

Figure CN119082586B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high entropy alloys, and in particular to a lightweight, high-strength, heat-resistant high entropy alloy, and also to a method for preparing the lightweight, high-strength, heat-resistant high entropy alloy. Background Art
[0002] Lightweight materials can reduce component weight, improve energy efficiency, conserve resources, and reduce environmental pollution. Consequently, lightweight structural material design has long attracted considerable attention. However, developing lightweight, yet strong and tough alloys has been a challenging task in materials research. Strength and ductility are typically mutually exclusive in metallic structural materials, and strength generally decreases with decreasing alloy density.
[0003] Currently, traditional lightweight alloy materials with low density and high specific strength primarily include Al, Mg, and Ti alloys. These alloys are widely used in the automotive, aerospace, and electronic components industries, making significant contributions to energy conservation. However, due to the limitations of traditional alloy design, the potential for compositional design and performance improvement is also limited, making further optimization of material properties difficult.
[0004] The room-temperature strength of Al- and Mg-based alloys typically does not exceed 800 MPa, and neither possesses good high-temperature resistance, making them difficult to operate at temperatures of 300°C or higher. Ti-based alloys exhibit strength-ductility mismatch, and titanium alloys only exhibit a certain strength below 600°C, making them difficult to operate at temperatures exceeding 600°C. These characteristics of lightweight alloys limit their further development and application in practical engineering fields.
[0005] Therefore, extreme service environments place more stringent requirements on lightweight structural materials, and it is necessary to develop lightweight, high-strength, and heat-resistant metal structural materials to meet the needs of precision equipment manufacturing and extreme service environments. Summary of the Invention
[0006] The purpose of the present disclosure is to provide a lightweight, high-strength, heat-resistant high-entropy alloy and a preparation method thereof, so as to solve the technical problem that it is difficult to simultaneously achieve low density, high strength and high temperature resistance in existing alloys.
[0007] In order to achieve the above-mentioned objectives, according to one aspect of the present disclosure, a lightweight, high-strength, heat-resistant, high-entropy alloy is provided. In terms of atomic percentage, the lightweight, high-strength, heat-resistant, high-entropy alloy contains Cr: 2-10%, Al: 5-15%, V: 10-20%, Nb: 5-20%, Ti: 40-60%, Zr: 2-10% and Si: 0.2-2.2%.
[0008] Furthermore, the lightweight, high-strength, heat-resistant high-entropy alloy comprises, in atomic percentage, Cr: 2-8%, Al: 8-12%, V: 12-20%, Nb: 8-20%, Ti: 40-55%, Zr: 2-8% and Si: 0.2-2.0%.
[0009] Furthermore, the lightweight, high-strength, heat-resistant high-entropy alloy includes, in atomic percentage, Cr: 2-8%, Al: 8-12%, V: 12-15%, Nb: 10-18%, Ti: 48-55%, Zr: 2-8% and Si: 0.2-2.0%.
[0010] Furthermore, the lightweight, high-strength, heat-resistant, high-entropy alloy satisfies 5% ≤ (Cr + Zr) ≤ 15% in atomic percentage.
[0011] Furthermore, the purity of the Cr, Al, V, Nb, Ti, Zr, and Si elemental raw materials used to form the lightweight, high-strength, heat-resistant high-entropy alloy exceeds 99.9 wt%.
[0012] According to another aspect of the present disclosure, a method for preparing the lightweight, high-strength, heat-resistant, high-entropy alloy of the present invention is provided, the method comprising the following steps: step S1, providing raw materials of Cr, Al, V, Nb, Ti, Zr, and Si, and polishing to remove the surface oxide film to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials; step S2, placing the Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials in a vacuum arc furnace for smelting, obtaining an alloy ingot after cooling, and then smelting the alloy ingot again, wherein the single-substance materials are smelted 5-15 times in the vacuum arc furnace to obtain a molten alloy; and step S3, using a vacuum suction casting device to suction-cast the molten alloy into a copper mold, cooling to room temperature, and obtaining a finished ingot of the lightweight, high-strength, heat-resistant, high-entropy alloy.
[0013] Furthermore, the density of the finished ingot obtained in step S3 is less than 5.5 g / cm 3 .
[0014] Furthermore, the finished ingot obtained in step S3 has a BCC single-phase microstructure.
[0015] Furthermore, the finished ingot obtained in step S3 has a room temperature tensile strength of ≥ 1 GPa and an elongation of ≥ 10%; a high temperature tensile strength of ≥ 800 MPa at 600°C; and a high temperature tensile strength of ≥ 500 MPa at 800°C.
[0016] As mentioned above, the known prior art alloys have the technical problem of being difficult to achieve low density, high strength and high temperature resistance at the same time. According to the technical solution disclosed in the present invention, a lightweight, high-strength, heat-resistant high-entropy alloy and a preparation method thereof are provided. By adjusting the appropriate ratio of seven elements, Cr, Al, V, Nb, Ti, Zr and Si, the obtained lightweight, high-strength, heat-resistant high-entropy alloy has a BCC single-phase structure, and a Zr-Si strengthening phase is precipitated during the high-temperature smelting process, thereby obtaining a high-entropy alloy with low density (lightweight), high strength and high temperature resistance. The density of the lightweight, high-strength, heat-resistant high-entropy alloy of the present invention is less than 5.5 g / cm 3 , room temperature tensile strength ≥ 1 GPa, elongation ≥ 10%; high-temperature tensile strength ≥ 800 MPa at 600°C; and high-temperature tensile strength ≥ 500 MPa at 800°C. Therefore, the lightweight, high-strength, heat-resistant high-entropy alloy of the present invention simultaneously achieves excellent low density (lightweight), high strength, and high-temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0018] Figure 1 1 is the XRD pattern of the ingot according to Example 1 of the present invention.
[0019] Figure 2 is a SEM photograph of the ingot according to Example 1 of the present invention.
[0020] Figure 3 1 is a SEM photograph of the ingot after high-temperature treatment at 800° C. according to Example 1 of the present invention. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present disclosure will be described in detail below with reference to the embodiments.
[0022] In response to the deficiencies in the prior art mentioned in the background technology, a specific embodiment of the present disclosure provides a lightweight, high-strength, heat-resistant, high-entropy alloy. In terms of atomic percentage, the lightweight, high-strength, heat-resistant, high-entropy alloy contains Cr: 2-10%, Al: 5-15%, V: 10-20%, Nb: 5-20%, Ti: 40-60%, Zr: 2-10% and Si: 0.2-2.2%.
[0023] It has been discovered that by adjusting the proportions of the seven elements Cr, Al, V, Nb, Ti, Zr, and Si within the range of the present invention, a stable BCC (body-centered cubic) single-phase structure can be formed. The resulting lightweight, high-strength, heat-resistant, high-entropy alloy possesses a BCC single-phase structure, effectively improving the alloy's strength and ductility. This is due to the synergistic effect of the various elements in the alloy and the formation of the BCC single-phase structure, which effectively inhibits grain growth and improves the material's flow strength.
[0024] For example, the lightweight, high-strength, heat-resistant, high-entropy alloy comprises 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% Cr by atomic percentage. Preferably, the lightweight, high-strength, heat-resistant, high-entropy alloy comprises 2-8% Cr by atomic percentage, more preferably 5-7% Cr.
[0025] For example, the lightweight, high-strength, heat-resistant, high-entropy alloy comprises 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% Al by atomic percentage. Preferably, the lightweight, high-strength, heat-resistant, high-entropy alloy comprises 8-12% Al by atomic percentage, more preferably 10-12% Al.
[0026] For example, the lightweight, high-strength, heat-resistant, high-entropy alloy contains, by atomic percentage, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% V. Preferably, the lightweight, high-strength, heat-resistant, high-entropy alloy contains, by atomic percentage, 12-15% V, more preferably, 14-15% V.
[0027] For example, the lightweight, high-strength, heat-resistant, high-entropy alloy comprises 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% Nb by atomic percentage. Preferably, the lightweight, high-strength, heat-resistant, high-entropy alloy comprises 10-18% Nb by atomic percentage, more preferably 15-18% Nb.
[0028] For example, the lightweight, high-strength, heat-resistant high-entropy alloy comprises 40%, 42%, 44%, 46%, 48%, 49%, 49.6%, 50%, 51%, 51.8%, 52%, 53%, 54%, 55%, 56%, 58%, 60% Ti. Preferably, the lightweight, high-strength, heat-resistant high-entropy alloy comprises 48-55% Ti by atomic percentage, more preferably 49.6-51.8% Ti.
[0029] For example, the lightweight, high-strength, heat-resistant, high-entropy alloy contains 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% Zr. Preferably, the lightweight, high-strength, heat-resistant, high-entropy alloy contains 2-8% Zr by atomic percentage, more preferably 4-5% Zr.
[0030] For example, the lightweight, high-strength, heat-resistant high-entropy alloy comprises 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% Si. Preferably, the lightweight, high-strength, heat-resistant high-entropy alloy comprises 0.2-2% Si by atomic percentage, more preferably 0.4-1% Si.
[0031] In some examples, the lightweight, high-strength, heat-resistant high-entropy alloy includes, by atomic percentage, Cr: 2-8%, Al: 8-12%, V: 12-20%, Nb: 8-20%, Ti: 40-55%, Zr: 2-8%, and Si: 0.2-2.0%.
[0032] In some examples, the lightweight, high-strength, heat-resistant high-entropy alloy includes, by atomic percentage, Cr: 2-8%, Al: 8-12%, V: 12-15%, Nb: 10-18%, Ti: 48-55%, Zr: 2-8%, and Si: 0.2-2.0%.
[0033] Furthermore, the specific elemental ratios of the present invention facilitate the precipitation of Zr-Si strengthening phases during the high-temperature smelting process of the individual raw materials. Under high-temperature conditions of 600°C and 800°C, the lightweight, high-strength, heat-resistant, high-entropy alloy of the present invention exhibited tensile strengths exceeding 800 MPa and 500 MPa, respectively, and maintained high-temperature elongation (13% and 61%, respectively). This is due to the Zr-Si strengthening phases formed within the alloy. These strengthening phases are stable at high temperatures, effectively improving the alloy's high-temperature mechanical properties and enabling the material to maintain stable operating conditions in extreme service environments.
[0034] Due to the specific ratio of elements such as Ti, Al and Zr, the obtained lightweight, high-strength, heat-resistant high-entropy alloy has a low density (less than 5.5 g / cm 3 ), achieving significantly superior performance compared to conventional Ti, Al, and Mg alloys, making it particularly suitable for weight-sensitive applications such as aerospace, high-performance automobiles, and precision electronic equipment. Therefore, through a rational elemental composition, the lightweight, high-strength, heat-resistant high-entropy alloy of this invention significantly improves its lightweight, high-strength, and high-temperature resistance, providing a new high-performance metal structural material for the high-end equipment manufacturing industry.
[0035] In some embodiments, the lightweight, high-strength, heat-resistant, high-entropy alloy satisfies the requirement of 5% ≤ (Cr + Zr) ≤ 15% in atomic percentage. When the sum of the atomic percentages of Cr and Zr in the lightweight, high-strength, heat-resistant, high-entropy alloy is within the range disclosed herein, the alloy's microstructure can be better controlled during preparation, thereby optimizing the alloy's overall performance. The sum of the atomic percentages of Cr and Zr within the aforementioned range also ensures that other elements, such as Al, V, Nb, Ti, and Si, can be more effectively dissolved in the matrix during smelting and post-processing, forming a uniform solid solution. This allows for a complex solution and precipitation mechanism to yield a high-strength, high-temperature-resistant, lightweight high-entropy alloy.
[0036] In some examples, the purity of the elemental raw materials of Cr, Al, V, Nb, Ti, Zr, and Si used to form the lightweight, high-strength, heat-resistant, high-entropy alloy exceeds 99.9 wt %. When the purity of the elemental raw materials used to smelt the lightweight, high-strength, heat-resistant, high-entropy alloy is within the range disclosed herein, the introduction of impurities can be reduced, the formation of second phases during alloy smelting can be avoided, unnecessary side reactions during smelting can be reduced, and the accuracy and consistency of the alloy composition can be ensured, thereby helping to improve the performance stability of the final product.
[0037] According to another embodiment of the present invention, a method for preparing the lightweight, high-strength, heat-resistant, high-entropy alloy of the present invention is provided, the method comprising the following steps: step S1, providing raw materials of Cr, Al, V, Nb, Ti, Zr, and Si, and removing the surface oxide film by grinding to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials; step S2, placing the Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials in a vacuum arc furnace for smelting, obtaining an alloy ingot after cooling, and then smelting the alloy ingot again, wherein the single-substance materials are smelted 5-15 times in the vacuum arc furnace to obtain a molten alloy; and step S3, using a vacuum suction casting device to suction-cast the molten alloy into a copper mold, cooling to room temperature, and obtaining a finished ingot of a lightweight, high-strength, heat-resistant, high-entropy alloy.
[0038] The present invention adopts vacuum arc melting and vacuum suction casting process, and by adjusting the specific content ratio of Cr, Al, V, Nb, Ti, Zr, and Si elements, it achieves lightweight alloy while maintaining high strength and high plasticity. The multi-element synergistic effect makes the tensile strength of the alloy reach more than 1 GPa at room temperature, and the elongation is greater than 10%. At the same time, the tensile strength at high temperatures of 600°C and 800°C reaches more than 800 MPa and 500 MPa respectively, showing excellent high-temperature strength and plasticity. In addition, the specific content ratio of Cr, Al, V, Nb, Ti, Zr, and Si elements can effectively control the microstructure of the alloy, forming a BCC single-phase structure, which is beneficial to improving the overall performance of the alloy. During the smelting process, the specific content ratio of Zr and Si elements is conducive to the precipitation of Zr-Si strengthening phase in the alloy. The formation of strengthening phase can improve the strength and heat resistance of the alloy, so that it can still maintain high mechanical properties at high temperatures.
[0039] In some embodiments, the density of the finished ingot obtained in step S3 is less than 5.5 g / cm 3 For example, the density of the finished ingot is 5.48 g / cm 3 , 5.46 g / cm 3 , 5.44 g / cm 3 , 5.41 g / cm 3 , 5.38 g / cm 3 , 5.35 g / cm 3 , 5.33g / cm 3 , 5.30 g / cm 3 , 5.28 g / cm 3 , 5.26 g / cm 3 , 5.24 g / cm 3 Preferably, the density of the finished ingot is 5.02 g / cm 3 to 5.38 g / cm 3 within the range.
[0040] In some examples, the finished ingot obtained in step S3 has a BCC single-phase microstructure.
[0041] In some examples, the finished ingot obtained in step S3 has a room temperature tensile strength of ≥ 1 GPa and an elongation of ≥ 10%; a high temperature tensile strength of ≥ 800 MPa at 600°C; and a high temperature tensile strength of ≥ 500 MPa at 800°C. For example, the room temperature tensile strength of the finished ingot is 1056 MPa, 1088 MPa, 1090 MPa, 1100 MPa, etc., and the elongation is 10%, 11%, 12.5%, or 15%. For example, the high temperature tensile strength of the finished ingot at 600°C is 825 MPa, 840 MPa, 855 MPa, 886 MPa, etc. For example, the high temperature tensile strength of the finished ingot at 800°C is 590 MPa, 510 MPa, 620 MPa, 697 MPa, etc.
[0042] The present application is further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application.
[0043] Example 1
[0044] The lightweight, high-strength, heat-resistant, high-entropy alloy of Example 1 comprises, in atomic percentage, Cr: 5%, Al: 10%, V: 15%, Nb: 15%, Ti: 49.6%, Zr: 5%, and Si: 0.4%.
[0045] The specific steps of its preparation method are as follows:
[0046] Step S1, providing Cr, Al, V, Nb, Ti, Zr, and Si single-substance raw materials, and polishing the surfaces of these single-substance raw materials to remove surface oxide films to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials.
[0047] Step S2: Place the single-element materials of Cr, Al, V, Nb, Ti, Zr, and Si in a vacuum arc furnace for smelting according to the ratio of the above alloy components, and obtain an alloy ingot after cooling to room temperature. Then, the alloy ingot is smelted again, and the smelting is repeated 5 times to obtain a molten alloy.
[0048] Step S3: Using a vacuum suction casting device, the molten alloy is suction-casted into a copper mold, and rapidly cooled to room temperature at a rate of approximately 1500°C / s, thereby obtaining a finished high-entropy alloy ingot.
[0049] The obtained high entropy alloy finished ingot structure formula is Cr5Al 10 V 15 Nb 15 Ti 49.6 Zr5Si 0.4 , the density of the alloy is 5.38 g / cm 3 , and has a BCC single-phase structure (such as Figure 1 As shown), the obtained Cr5Al 10 V 15 Nb 15 Ti 49.6 Zr5Si 0.4 The room temperature tensile strength of the alloy is 1056 MPa, and the elongation is 10%; the high temperature tensile strength at 600°C is 855 MPa, and the elongation is 13%; and the high temperature tensile strength at 800°C is 697 MPa, and the elongation is 61% (Table 1).
[0050] Example 2
[0051] The lightweight, high-strength, heat-resistant, high-entropy alloy of Example 2 comprises, in atomic percentage, Cr: 7%, Al: 12%, V: 12%, Nb: 10%, Ti: 55%, Zr: 2%, and Si: 2%.
[0052] The specific steps of its preparation method are as follows:
[0053] Step S1, providing Cr, Al, V, Nb, Ti, Zr, and Si single-substance raw materials, and polishing the surfaces of these single-substance raw materials to remove surface oxide films to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials.
[0054] Step S2: Place the single-element materials of Cr, Al, V, Nb, Ti, Zr, and Si in a vacuum arc furnace for smelting according to the ratio of the above alloy components, and obtain an alloy ingot after cooling to room temperature. Then, the alloy ingot is smelted again, and the smelting is repeated 5 times to obtain a molten alloy.
[0055] Step S3: Using a vacuum suction casting device, the molten alloy is suction-casted into a copper mold, and rapidly cooled to room temperature at a rate of approximately 1500°C / s, thereby obtaining a finished high-entropy alloy ingot.
[0056] The obtained high entropy alloy finished ingot structure formula is Cr7Al 12 V 12 Nb 10 Ti 55 Zr2Si2, the density of the alloy is 5.02g / cm 3 , and has a BCC single-phase structure (such as Figure 1 As shown), the obtained Cr7Al 12 V 12 Nb 10 Ti 55The room temperature tensile strength of the Zr2Si2 alloy is 1100 MPa, and the elongation is 12.5%; the high temperature tensile strength at 600°C is 825 MPa, and the elongation is 16%; the high temperature tensile strength at 800°C is 510 MPa, and the elongation is 22% (Table 1).
[0057] Example 3
[0058] The lightweight, high-strength, heat-resistant, high-entropy alloy of Example 3 comprises, in atomic percentage, Cr: 2%, Al: 12%, V: 15%, Nb: 18%, Ti: 48%, Zr: 4%, and Si: 1%.
[0059] The specific steps of its preparation method are as follows:
[0060] Step S1, providing Cr, Al, V, Nb, Ti, Zr, and Si single-substance raw materials, and polishing the surfaces of these single-substance raw materials to remove surface oxide films to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials.
[0061] Step S2: Place the single-element materials of Cr, Al, V, Nb, Ti, Zr, and Si in a vacuum arc furnace for smelting according to the ratio of the above alloy components, and obtain an alloy ingot after cooling to room temperature. Then, the alloy ingot is smelted again, and the smelting is repeated 15 times to obtain a molten alloy.
[0062] Step S3: Using a vacuum suction casting device, the molten alloy is suction-casted into a copper mold, and rapidly cooled to room temperature at a rate of approximately 1500°C / s, thereby obtaining a finished high-entropy alloy ingot.
[0063] The obtained high entropy alloy finished ingot structure formula is Cr2Al 12 V 15 Nb 18 Ti 48 The density of Zr4Si alloy is 5.37g / cm 3 , and has a BCC single-phase structure (such as Figure 1 As shown), the obtained Cr2Al 12 V 15 Nb 18 Ti 48 The room temperature tensile strength of the Zr4Si alloy is 1088 MPa, and the elongation is 11%; the high temperature tensile strength at 600°C is 886 MPa, and the elongation is 23%; and the high temperature tensile strength at 800°C is 620 MPa, and the elongation is 30% (Table 1).
[0064] Example 4
[0065] The lightweight, high-strength, heat-resistant, high-entropy alloy of Example 4 comprises, in atomic percentage, Cr: 8%, Al: 8%, V: 14%, Nb: 10%, Ti: 51.8%, Zr: 8%, and Si: 0.2%.
[0066] The specific steps of its preparation method are as follows:
[0067] Step S1, providing Cr, Al, V, Nb, Ti, Zr, and Si single-substance raw materials, and polishing the surfaces of these single-substance raw materials to remove surface oxide films to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials.
[0068] Step S2: Place the single-element materials of Cr, Al, V, Nb, Ti, Zr, and Si in a vacuum arc furnace for smelting according to the ratio of the above alloy components, and obtain an alloy ingot after cooling to room temperature. Then, the alloy ingot is smelted again, and the smelting is repeated 10 times to obtain a molten alloy.
[0069] Step S3: Using a vacuum suction casting device, the molten alloy is suction-casted into a copper mold, and rapidly cooled to room temperature at a rate of approximately 1500°C / s, thereby obtaining a finished high-entropy alloy ingot.
[0070] The obtained high entropy alloy finished ingot structure formula is Cr8Al8V 14 Nb 10 Ti 51.8 Zr8Si 0.2 , the density of the alloy is 5.33g / cm 3 , and has a BCC single-phase structure (such as Figure 1 As shown), the obtained Cr8Al8V 14 Nb 10 Ti 51.8 Zr8Si 0.2 The room temperature tensile strength of the alloy is 1090 MPa, and the elongation is 15%; the high temperature tensile strength at 600°C is 840 MPa, and the elongation is 45%; and the high temperature tensile strength at 800°C is 590 MPa, and the elongation is 30% (Table 1).
[0071] Comparative Example 1
[0072] The high entropy alloy of Comparative Example 1 includes, in atomic percentage, Cr: 1%, Al: 10%, V: 15%, Nb: 15%, Ti: 57.6%, Zr: 1%, and Si: 0.4%.
[0073] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0074] The obtained high entropy alloy finished ingot structure formula is CrAl 10V 15 Nb 15 Ti 57.6 ZrSi 0.4 , the density of the alloy is 5.2 g / cm 3 , forming a BCC organizational structure; the room temperature tensile strength is 688 MPa, and the elongation is 21%; the high temperature tensile strength at 600°C is 450 MPa, and the elongation is 13%; the high temperature tensile strength at 800°C is 80 MPa, and the elongation is 15%.
[0075] Comparative Example 2
[0076] The high entropy alloy of Comparative Example 2 includes, in atomic percentage, Cr: 12%, Al: 4%, V: 15%, Nb: 15%, Ti: 48.6%, Zr: 5%, and Si: 0.4%.
[0077] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0078] The obtained high entropy alloy finished ingot structure formula is Cr 12 Al4V 15 Nb 15 Ti 48.6 Zr5Si 0.4 , the density of the alloy is 5.65 g / cm 3 , forming a BCC organizational structure; the room temperature tensile strength is 827 MPa, and the elongation is 7%; the high temperature tensile strength at 600°C is 863 MPa, and the elongation is 17%; the high temperature tensile strength at 800°C is 702 MPa, and the elongation is 62%.
[0079] Comparative Example 3
[0080] The high entropy alloy of Comparative Example 3 includes, in atomic percentage, Cr: 5%, Al: 18%, V: 15%, Nb: 15%, Ti: 34.6%, Zr: 12%, and Si: 0.4%.
[0081] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0082] The obtained high entropy alloy finished ingot structure formula is Cr5Al 18 V 15 Nb 15 Ti 34.6 Zr 12 Si 0.4 The density of the alloy is 5.42 g / cm 3, forming BCC and B2 organizational structures; the room temperature tensile strength is 1121 MPa, and the elongation is 5%; the high temperature tensile strength at 600°C is 505 MPa, and the elongation is 12%; the high temperature tensile properties at 800°C cannot be measured because it cannot withstand the high temperature of 800°C.
[0083] Comparative Example 4
[0084] The high entropy alloy of Comparative Example 4 includes, in atomic percentage, Cr: 5%, Al: 10%, V: 8%, Nb: 3%, Ti: 68.6%, Zr: 5%, and Si: 0.4%.
[0085] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0086] The obtained high entropy alloy finished ingot structure formula is Cr5Al 10 V8Nb3Ti 68.6 Zr5Si 0.4 The density of the alloy is 4.78 g / cm 3 , forming a BCC organizational structure; the room temperature tensile strength is 1002 MPa, and the elongation is 10.5%; the high temperature tensile strength at 600°C is 205 MPa, and the elongation is 11%; the high temperature tensile properties at 800°C cannot be measured because it cannot withstand the high temperature of 800°C.
[0087] Comparative Example 5
[0088] The high entropy alloy of Comparative Example 5 includes, in atomic percentage, Cr: 5%, Al: 10%, V: 22%, Nb: 15%, Ti: 42.6%, Zr: 5%, and Si: 0.4%.
[0089] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0090] The obtained high entropy alloy finished ingot structure formula is Cr5Al 10 V 22 Nb 15 Ti 42.6 Zr5Si 0.4 The density of the alloy is 5.49 g / cm 3 , forming a BCC organizational structure; the room temperature tensile strength is 795 MPa, and the elongation is 27%; the high temperature tensile strength at 600°C is 425 MPa, and the elongation is 7%; the high temperature tensile properties at 800°C cannot be measured because it cannot withstand the high temperature of 800°C.
[0091] Comparative Example 6
[0092] The high entropy alloy of Comparative Example 6 includes, in atomic percentage, Cr: 5%, Al: 10%, V: 15%, Nb: 22%, Ti: 42.6%, Zr: 5%, and Si: 0.4%.
[0093] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0094] The obtained high entropy alloy finished ingot structure formula is Cr5Al 10 V 15 Nb 22 Ti 42.6 Zr5Si 0.4 , the density of the alloy is 5.68 g / cm 3 , forming a BCC microstructure; the room temperature tensile strength is 927 MPa, and the elongation is 8%; the high temperature tensile strength at 600°C is 790 MPa, and the elongation is 15%; the high temperature tensile strength at 800°C is 610 MPa, and the elongation is 63%.
[0095] Comparative Example 7
[0096] The high entropy alloy of Comparative Example 7 includes, in atomic percentage, Cr: 5%, Al: 10%, V: 15%, Nb: 15%, Ti: 40.5%, Zr: 12%, and Si: 2.5%.
[0097] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0098] The obtained high entropy alloy finished ingot structure formula is Cr5Al 10 V 15 Nb 15 Ti 40.5 Zr 12 Si 2.5 , the density of the alloy is 5.50 g / cm 3 , forming BCC and B2 organizational structures; the room temperature tensile strength is 1100 MPa, and the elongation is 7%; the high temperature tensile strength at 600°C is 460 MPa, and the elongation is 15%; the high temperature tensile properties at 800°C cannot be measured because it cannot withstand the high temperature of 800°C.
[0099] Comparative Example 8
[0100] The high entropy alloy of Comparative Example 8 includes, in atomic percentage, Cr: 5%, Al: 10%, V: 15%, Nb: 15%, Ti: 49.9%, Zr: 5%, and Si: 0.1%.
[0101] The preparation method is the same as that of Example 1, the only difference being the ratio of the alloy components.
[0102] The obtained high entropy alloy finished ingot structure formula is Cr5Al 10 V 15 Nb 15 Ti 49.9 Zr5Si 0.1 , the density of the alloy is 5.39 g / cm 3 , forming a BCC organizational structure; the room temperature tensile strength is 930 MPa, and the elongation is 11%; the high temperature tensile strength at 600°C is 725 MPa, and the elongation is 35%; the high temperature tensile strength at 800°C is 580 MPa, and the elongation is 22%.
[0103] Table 1 Density, phase structure, tensile strength and elongation of finished ingots of Examples 1-4
[0104]
[0105] Table 2 Density, phase structure, tensile strength and elongation of finished ingots of Comparative Examples 1-8
[0106]
[0107] The above results show that the high-entropy alloys of Examples 1-4, which contain the seven elements in the specific ratios of the present invention, exhibit low density, high room-temperature tensile strength, and excellent high-temperature tensile strength. In contrast, the comparative examples, which do not contain the seven elements in the specific ratios of the present invention, exhibit high density, lack lightweight properties, and / or exhibit poor tensile strength and elongation at both room and high temperatures.
[0108] The above embodiments are merely descriptions of the technical solutions of the present disclosure, and are not intended to limit the scope thereof. Although a person skilled in the art may make various modifications based on the above examples, such modifications shall fall within the scope of protection of the present disclosure as long as they do not depart from the spirit of the present disclosure.
[0109] It should be noted that the terms "first," "second," and the like in the specification and claims of this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or precedence. It should be understood that the terms used in this manner are interchangeable where appropriate, so that the embodiments of the application described herein can, for example, be implemented in an order other than that described herein.
[0110] The foregoing description relates only to specific embodiments of the present disclosure and is not intended to limit the present disclosure. Those skilled in the art will readily appreciate that the present disclosure is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present disclosure shall be within the scope of protection of the present disclosure.
Claims
1. A lightweight, high-strength, heat-resistant, high-entropy alloy, characterized in that: In terms of atomic percentage, the lightweight, high-strength, heat-resistant high-entropy alloy comprises Cr: 2-10%, Al: 5-15%, V: 10-20%, Nb: 5-20%, Ti: 40-60%, Zr: 2-10% and Si: 0.2-2.2%, and the density of the high-entropy alloy is less than 5.5 g / cm 3 , room temperature tensile strength ≥ 1 GPa, elongation ≥ 10%; 600°C high temperature tensile strength ≥ 800 MPa; and 800°C high temperature tensile strength ≥ 500 MPa.
2. The lightweight, high-strength, heat-resistant, high-entropy alloy according to claim 1, characterized in that: In terms of atomic percentage, the lightweight, high-strength, heat-resistant and high-entropy alloy contains Cr: 2-8%, Al: 8-12%, V: 12-20%, Nb: 8-20%, Ti: 40-55%, Zr: 2-8% and Si: 0.2-2.0%.
3. The lightweight, high-strength, heat-resistant, high-entropy alloy according to claim 1, characterized in that: In terms of atomic percentage, the lightweight, high-strength, heat-resistant and high-entropy alloy contains Cr: 2-8%, Al: 8-12%, V: 12-15%, Nb: 10-18%, Ti: 48-55%, Zr: 2-8% and Si: 0.2-2.0%.
4. The lightweight, high-strength, heat-resistant, high-entropy alloy according to any one of claims 1 to 3, characterized in that: In terms of atomic percentage, the lightweight, high-strength, heat-resistant, high-entropy alloy satisfies 5% ≤ (Cr + Zr) ≤ 15%.
5. The lightweight, high-strength, heat-resistant, high-entropy alloy according to any one of claims 1 to 3, characterized in that: The purity of the single element raw materials of Cr, Al, V, Nb, Ti, Zr and Si used to form the lightweight, high-strength, heat-resistant and high-entropy alloy exceeds 99.9 wt%.
6. A method for preparing a lightweight, high-strength, heat-resistant, high-entropy alloy according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Step S1, providing raw materials of Cr, Al, V, Nb, Ti, Zr, and Si, and removing the surface oxide film by grinding to obtain Cr, Al, V, Nb, Ti, Zr, and Si single-substance materials; Step S2, placing the single-substance materials of Cr, Al, V, Nb, Ti, Zr, and Si in a vacuum arc furnace for smelting, obtaining an alloy ingot after cooling, and then smelting the alloy ingot again, wherein the single-substance materials are smelted 5-15 times in the vacuum arc furnace to obtain a molten alloy; and Step S3, using vacuum suction casting equipment to suction cast the molten alloy into a copper mold, cooling it to room temperature, and obtaining a finished ingot of the lightweight, high-strength, heat-resistant, high-entropy alloy.
7. The method according to claim 6, characterized in that The density of the finished ingot obtained in step S3 is less than 5.5 g / cm 3 .
8. The method according to claim 6 or 7, characterized in that: The finished ingot obtained in step S3 has a BCC single-phase microstructure.
9. The method according to claim 6 or 7, characterized in that: The finished ingot obtained in step S3 has a room temperature tensile strength of ≥ 1 GPa, an elongation of ≥ 10%; a high temperature tensile strength of 600°C of ≥ 800 MPa; and a high temperature tensile strength of 800°C of ≥ 500 MPa.
Citation Information
Patent Citations
Lightweight high-entropy alloy with high strength and high plasticity and preparation method thereof
CN109402482A